E-Services In The E-Government: Bibliometric Analysis Of International Articles - Zittei, Marcus Vinicius Moreira; Fernandes, Francisco Carlos (Future Studies Research Journal: Trends and Strategies, 2015)
In the present study, the objective was to analyze the production and the publications profile of the theme: e-services tools referring to eGovernment in the Scopus database, for the period as from 2001 through 2015. The electronic government includes tools for the government's relationship with society, citizens, other governments and businesses. The focus of these articles includes e-services and e-Government activities for the businesses. It was used descriptive research, conducted through literature review, with bibliometric approach and quantitative analysis, with sample collected in the Scopus database. It was found that the number of works in this period was 299, of which 45 papers published in events in 2010 and 16 articles published in journals in 2013. The core point of the articles with the highest citation is related to the deployment and the users’ awareness on tools established by countries.